Engineering cancer cell membrane-camouflaged metal complex for efficient targeting therapy of breast cancer - Xiaoying Li; Yanzi Yu; Qi Chen; Jiabao Lin; Xueqiong Zhu; Xiaoting Liu; Lizhen He; Tianfeng Chen; Weiling He (Journal of Nanobiotechnology, 2022)
Abstract Background Cancer cell membrane-camouflaged nanotechnology for metal complex can enhance its biocompatibility and extend the effective circulation time in body. The ruthenium polypyridyl complex (RuPOP) has extensive antitumor activity, but it still has disadvantages such as poor biocompatibility, lack of targeting, and being easily metabolized by the organism. Cancer cell membranes retain a large number of surface antigens and tumor adhesion molecules CD47, which can be used to camouflage the metal complex and give it tumor homing ability and high biocompatibility. Results Therefore, this study provides an electrostatic adsorption method, which uses the electrostatic interaction of positive and negative charges between RuPOP and cell membranes to construct a cancer cell membrane-camouflaged nano-platform (RuPOP@CM). Interestingly, RuPOP@CM maintains the expression of surface antigens and tumor adhesion molecules, which can inhibit the phagocytosis of macrophage, reduce the clearance rate of RuPOP, and increase effective circulation time, thus enhancing the accumulation in tumor sites. Besides, RuPOP@CM can enhance the activity of cellular immune response and promote the production of inflammatory cytokines including TNF-α, IL-12 and IL-6, which is of great significance in treatment of tumor. On the other hand, RuPOP@MCM can produce intracellular ROS overproduction, thereby accelerating the apoptosis and cell cycle arrest of tumor cells to play an excellent antitumor effect in vitro and in vivo. Conclusion In brief, engineering cancer cell membrane-camouflaged metal complex is a potential strategy to improve its biocompatibility, biological safety and antitumor effects.